Analisis Bibliometrik ANALISIS BIBLIOMETRIK: TREN DAN PERSPEKTIF PENELITIAN PENDIDIKAN PEDAGOGI DI ERA DIGITAL (2014-2024) - Sumara, Andry Rivan; Yusrizal; Arsyad; Budiwati, Neti (FEB Universitas Sam Ratulangi Manado, 2025)
The examination of pedagogy is crucial due to its substantial influence on educational learning frameworks. Digital advancements profoundly affect pedagogical methodologies. Consequently, comprehensive investigations regarding pedagogical research trends in the digital era over the past ten years are essential. A bibliometric analysis seeks to delineate research pertaining to pedagogy within the digital context. Data is sourced from the Scopus database, focusing on educational and digital subjects, specifically through queries of